BAKTI SOSIAL SEKOLAH TINGGI TEOLOGI TABGHA BATAM DAN CAHAYA OBOR BERKAT DI MALL POLLUX HABIBIE BATAM CENTER - Pasaribu, George Rudi Hartono; Steven; Suhendra, Suhendra (JURNAL BEATITUDES, 2024)
The social service event organized by the Tabgha Theological College of Batam and the Cahaya Obor Berkat Foundation from August 9-11, 2024, at Pollux Habibie Mall, Batam Center, is a community service initiative in celebration of the 79th Independence Day of the Republic of Indonesia. This event included free general health check-ups and medical treatment, IVA (Visual Inspection with Acetic Acid) screenings for early detection of cervical cancer, and the distribution of 500 staple food packages to those in need. The main objectives were to provide healthcare access to underprivileged communities, raise awareness about the importance of early disease prevention, and alleviate the economic burden on citizens. The event was conducted in collaboration with the Batam City Health Office and Puskesmas Baloi Permai. As a result, 700 people received health services, 150 women underwent IVA screenings, and 500 food packages were distributed. This social service positively impacted the health and well-being of the community, embodying the spirit of independence through tangible acts of service.